Profil Kemampuan Berpikir Kritis Siswa Pada Konsep Keanekaragaman Hayati Melalui Problem Based Learning - Erwanto, Erwanto (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to describe the profile of students' critical thinking skills on the concept of biodiversity through Problem Based Learning. The research method used quantitative descriptive research. The population in this study was students of SMA Negeri 1 Moga consisting of 36 students of class X MIPA 5 SMA Negeri 1 Moga Pemalang Regency of odd semester 2020/2021 academic year as the samples. The research instrument used was a test to obtain data, which was described in indicators of critical thinking skills. The data collected were then analyzed using descriptive statistics for presentation and students' critical thinking skills. Based on the results of the study, it can be revealed that students' critical thinking skills on the concept of biodiversity through Problem Based Learning were that providing a simple explanation reached 65.97%, building basic skills 62.15%, making conclusion 57.64%, providing further explanations 57.64%, and managing strategies and techniques 61.11%.